Clinical case: aortic valve replacement with aortic root reconstruction and coronary artery bypass grafting in 73-yo obese female patient - D. V. Borisov; A. S. Zotov; S. A. Vachev; A. V. Troitskiy; R. I. Khabazov (Клиническая практика, 2018)
Aortic valve replacement is the second most common cardiac surgery procedure. Prosthesis-patient size mismatch can increase the incidence of adverse events postoperatively, it also leads to increased left ventricular load. Some studies describe the higher mortality in this group of patients. It is also proved that patients with severe aortic stenosis usually have impaired platelet aggregation and low von Willebrand factor causing bleeding disorders.